The Position of Sociology in a Transitional Society - Čaldarović Ognjen (Array, 2006)
In this work accent was given to the perspective of the sociology in transitional society, in this case - in Croatia.There is posibility that sociology, as a science, can be factor of stabilization in the development of the society.